High efficient alternating anaerobic/aerobic process for polyester resin wastewater treatment : performance and microbial community structure - Sun Faqian (2020)
This study investigated organics removal and microbial community in a two-stage alternating anaerobic/aerobic (A1/O1/A2/O2) process for polyester resin wastewater treatment. It was found that chemical oxygen demand (COD) concentration could be reduced to below 500 mg L−1 from 12,880 mg L−1 with average COD removal rate of 2.79, 4.37, 0.50 and 0.97 kg m−3 d−1 in four reactors, respectively. Two important chemical compounds in the wastewater, namely, purified terephthalic acid (PTA) (625 mg L−1) and phenol (480 mg L−1), did not display inhibitory effects on COD removal while they were almost completely degraded in the first-stage A/O process. Further, the majority of esters, alkanes, phenols, acids and alcohols could be removed in the system. However, two hazardous refractory compounds, 5,5-dimethyl-1,3-dioxane and 1,4-dioxane, were still present as major components in the final effluent. 16S rRNA high-throughput sequencing results revealed that a distinct preference of selected bacterial groups towards anaerobic/aerobic reactors and operating conditions. High abundance of Lewinella genus (2.4–34.0%), which was correlated to ester-hydrolyzing ability, may play an important role in the high efficiency of organics removal.